Deskeletonizing the Sigmoid Sinus Is Noncompulsory in Skull Base Surgery: 3D Modeling of the Translabyrinthine Approach - Samlal, Djenghiz P. S.; Voormolen, Eduard H. J.; Thomeer, Hans G. X. M. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Sigmoid sinus (SS) compression and injury is associated with postoperative SS occlusion and corresponding morbidity. Leaving the SS skeletonized with a thin boney protection during surgery might be favorable. This study quantifies the effect of the SS position on the operative exposure in the translabyrinthine approach and assesses the feasibility of retracting a skeletonized SS.Twelve translabyrinthine approaches were performed on cadaveric heads with varying SS retraction: skeletonized stationary (TL-S), skeletonized posterior retraction (TL-R), and deskeletonized collapsing of the sinus (TL-C). High-definition three-dimensional reconstruction of the resection cavity was obtained. The primary outcome, “surgical freedom” (mm2), was the area at the level of the craniotomy from which the internal acoustic porus could be reached in an unobstructed straight line. Secondary outcomes include the “exposure angle,” “angle of attack,” and presigmoid depth.During TL-R, surgical freedom increased by a mean of 41% (range: 9–92%, standard deviation [SD]: 28) when compared to no retraction (TL-S). Collapsing the SS in TL-C provided a mean increase of 52% (range: 19–95%, SD: 22) compared to TL-S. In most cases, the exposure is the greatest when the SS is collapsed. In 40% of the specimens, the provided exposure while retracting (TL-R) instead of collapsing (TL-S) the sinus is equal or greater than 50% of other specimens in which the sinus is collapsed.In cases with favorable anatomy, a translabyrinthine resection in which the skeletonized SS is retracted provides comparably sufficient exposure for adequate and safe tumor resection.
Keywords: skull base; cerebellopontine; 3D modeling; anatomy; cadaveric; surgical exposure; sigmoid sinus; sinus thrombosis